Nanostructure-directed chemical sensing: The IHSAB principle and the dynamics of acid/base-interface interaction - Gole, James L.; Laminack, William (Beilstein Journal of Nanotechnology, 2013)
Nanostructure-decorated n-type semiconductor interfaces are studied in order to develop chemical sensing with nanostructured materials. We couple the tenets of acid/base chemistry with the majority charge carriers of an extrinsic semiconductor. Nanostructured islands are deposited in a process that does not require self-assembly in order to direct a dominant electron-transduction process that forms the basis for reversible chemical sensing in the absence of chemical-bond formation. Gaseous analyte interactions on a metal-oxide-decorated n-type porous silicon interface show a dynamic electron transduction to and from the interface depending upon the relative strength of the gas and metal oxides. The dynamic interaction of NO with TiO2, SnO2, NiO, CuxO, and AuxO (x >> 1), in order of decreasing acidity, demonstrates this effect. Interactions with the metal-oxide-decorated interface can be modified by the in situ nitridation of the oxide nanoparticles, enhancing the basicity of the decorated interface. This process changes the interaction of the interface with the analyte. The observed change to the more basic oxinitrides does not represent a simple increase in surface basicity but appears to involve a change in molecular electronic structure, which is well explained by using the recently developed IHSAB model. The optical pumping of a TiO2 and TiO2−xNx decorated interface demonstrates a significant enhancement in the ability to sense NH3 and NO2. Comparisons to traditional metal-oxide sensors are also discussed.
Keywords: chemical sensors; gas interface interactions; IHSAB theory; nitrated oxides; porous silicon